Linear and non-linear video and TV applications using IPv6 and IPv6 multicast - Minoli, Daniel, 1952- (Wiley, 2012)
"This up-to-date resource explores evolving trends in the TV and video services industry, including worldwide deployment of IPv6, IPTV services, web-produced video content, and the plethora of different screens available from TV to iPad. The coverage offers practical suggestions on implementing these technologies in service provider networks to support the cost-effective delivery of entertainment, and how new revenue-generating services can be developed. With this innovative, future-oriented guide, a variety of readers will become familiar with the current and prospective technology and take advantage of its resulting new trends"--